Effect of green tea extract mouthrinse and probiotic mouthrinse on salivary pH in a group of schoolchildren: An in vivo study - Saranya Manikandan; Subasish Behera; Radhakrishnan Karthikeyan; Arumugasamy Niranjana; Rajendran Bharathan; Omar Farooq Burhanuddin Mohammed (Wolters Kluwer Medknow Publications, 2020)
Aim and Objective: The aim of the study was to assess the efficacy of probiotic and green tea mouthrinse on salivary pH. Materials and Methods: This study was conducted over a period of 1 month among 40 healthy schoolchildren aged between 6 and 8 years. The subjects who fulfilled inclusion criteria were selected and randomly divided into two groups, namely probiotic and green tea groups. Salivary pH was recorded at baseline (0 day) and at the end of the specified time using GC pH strips. Statistical analysis was done using paired t test. P < 0.05 was considered statistically significant. Result: The comparison of mean pH scores for green tea showed that the pH of saliva was increased in the children after rinsing with green tea (6.00-7.60) and was statistically significant (P < 0.001). Similarly, when pre- and post-mean pH was compared in the probiotic group, the pH was found to be higher in the probiotic rinse group (5.60-7.20). The results were statistically significant. Conclusion: The study conducted shows the beneficial effects of green tea in providing a alkaline environment, which is conducive to the oral health of children.